PENGEMBANGAN MEDIA APRON HITUNG DALAM PEMBELAJARAN BERHITUNG ANAK USIA 5-6 TAHUN DI TAMAN KANAK-KANAK SURYA BAHARI DESA MARGASARI KECAMATAN LABUHAN MARINGGAI KABUPATEN LAMPUNG TIMUR - Eni Wahyuti (UNISAN JURNAL, 2024)
The problem identified in this research is the lack of varied media support in the learning process for children according to their cognitive development characteristics related to numerical abilities in 5-6-year-old children. This study aims to: (1) produce counting apron media suitable for the characteristics of children in the B group of TK SURYA BAHARI, (2) determine the design of counting apron media to enhance numerical abilities in early childhood at TK SURYA BAHARI. This research is a development study using the ADDIE model consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. The methods used in this research are observation, interview, questionnaire, and documentation methods. The research instruments include observation guidelines, interviews, questionnaires, and documentation regarding the cognitive learning objectives. The results of the development research indicate that from the expert validation, the material expert assessment resulted in "very valid," the media expert assessment resulted in "very valid," the small group trial conducted with two students resulted in "very valid," and the large group trial with ten students resulted in "very valid." Thus, the development of counting apron media is designed according to children’s characteristics, making it suitable for enhancing numerical abilities in 5-6-year-old children at TK Surya Bahari. Keywords : Counting Apron Media, Numerical Abilities, 5-6-Year-Old Children